Analog and digital complete denture bases accuracy and dimensional stability: An in-vitro evaluation at 24 hours and 6 months - Casucci, Alessio; Verniani, Giulia; Bonadeo, Giovanni; Fadil, Sahin; Ferrari, Marco (Journal of dentistry, 2025)
The study aimed to evaluate the accuracy of 3D printed complete denture bases compared to analog and milling manufacturing. Denture bases (n = 60) were created using three methods: milling (n = 10), analog (flasking) (n = 10), and 3D printing (n = 40). The 3D printing group was further divided into subgroups and each of the material groups. All samples were scanned, and their surfaces were analyzed using 3D software (Geomagic Control X software, 3D Systems) to compare them to the reference model. The accuracy was assessed using root mean square (RMS) values, reflecting the average deviation between the denture bases and the reference model. At 24 h, the "Temp Print", from 3D printing group had the lowest RMS values (54.20±9.44 µm), indicating higher accuracy, while the "ProBase Hot" from the anlog group showed the highest discrepancies, particularly in the border areas. Over six months, all groups experienced increased RMS values, with the 3d pronted "Denture 3d+" group showing the most significant variations (194.1 ± 49.63 µm). The "Temp Print" group maintained the lowest RMS values, indicating better stability at 6 months. Despite some discrepancies, all denture bases remained within clinically acceptable limits (300 µm). Milled bases were the most stable between 24 h and six months. In terms of accuracy and stability, 3D printed resins are suitable for both prototypes and definitive dentures. Further research is required to confirm the clinical acceptability of these materials. Accuracy in the fabrication of denture bases is paramount for ensuring proper fit, function, and comfort for patients. Analog, addictive and subtractive manufacturing methods of production obtained good dentures accuracy.